Pengenalan Kearifan Lokal Dalam Pembuatan Kerupuk Gerandong Sebagai Sumber Belajar Siswa Sekolah Dasar - Fauziah, Amirotul; Widodo, Wahono; Istiq'faroh, Nurul (CV. Kurnia Grup, 2024)
This study aims to explore the local wisdom values embedded in the production of Kerupuk Gerandong as a source of character education for elementary school students. Amid the wave of globalization, local cultures are often marginalized, including traditional foods. Kerupuk Gerandong, as one of the local culinary products, not only offers a unique taste but also embodies social and cultural values relevant to education. Using a descriptive qualitative approach and literature review method, this research identifies values such as honesty, perseverance, hard work, independence, responsibility, and cooperation, which are reflected in each stage of the Kerupuk Gerandong production process. These values are expected to enrich character education and enhance students' understanding of the importance of preserving local culture. The integration of local wisdom into education also contributes to strengthening students' cultural identity and fostering an appreciation for local products from an early age. The findings reveal that learning based on local wisdom not only helps students grasp scientific concepts in real-life contexts but also develops beneficial social skills and character traits. Thus, utilizing Kerupuk Gerandong as a learning resource has the potential to support sustainable character education in Indonesia.